Teliospore morphology characterization of Uromycladium falcatariae in falcata plantations at different elevations in Mindanao Island, Philippines - MHAR O. LOQUEZ; CAROLINA D. AMPER; ADRIAN M. TULOD; DENNIS M. GILBERO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Loquez MO, Amper CD, Tulod AM, Gilbero DM. 2025. Teliospore morphology characterization of Uromycladium falcatariae in falcata plantations at different elevations in Mindanao Island, Philippines. Biodiversitas 26: 296-305. The fungus Uromycladium falcatariae causes gall rust disease in falcata (Falcataria falcata), with severe infections commonly observed at higher elevations (>400 masl). It produces teliospores that disperse through the air, contributing to its widespread prevalence. This study aimed to characterize the fungal teliospores across different elevations in Mindanao using Light Microscopy (LM) and Scanning Electron Microscopy (SEM). Mature galls with visible brown or rusty powder from falcata were collected from low (<400 masl), moderate (>400-800 masl), and high (>801 masl) elevations. Microphotographs of the teliospores were generated, examined, and compared for morpho-features and quantitative measurements across these elevations. This research provides the first SEM-based morphological characterization of U. falcatariae. The LM results revealed significant increases in teliospore length (P<0.05) and width (P<0.05) with elevation, with the largest dimensions observed at high elevations. SEM analysis demonstrated significant variation in the diameter of the germ pore (P<0.01) and the dorsal concave structure (P<0.05) across elevations, with the largest measurements recorded at high elevations. Detailed morphological features and quantitative measurements of teliospores were revealed from apical, dorsal, and equatorial orientations in SEM. Furthermore, this study provided morphological characteristics of teliospores across elevations, which can aid in the taxonomy and morphological classification of this rust fungus.